Pain, lactate, and anesthetics: intertwined regulators of tumor metabolism and immunity - Lan, Qinghai; Ouyang, Aiping; Chen, Yijian; Li, Youchun; Zhong, Baolin; Deng, Simin (Frontiers in Oncology, 2025)
Patients with advanced cancer frequently endure severe pain, which substantially diminishes their quality of life and can adversely impact survival. Analgesia, a critical modality for alleviating such pain, is now under scrutiny for its potential role in cancer progression, a relationship whose underlying mechanisms remain obscure. Emerging evidence suggests that lactate, once considered a metabolic byproduct, actively participates in the malignant progression of cancer by modulating both metabolic and immunological pathways within the tumor microenvironment. Furthermore, lactate is implicated in the modulation of cancer-related pain, exerting effects through direct and indirect mechanisms. This review synthesizes current understanding of lactate’s production, transport, and functional roles in tumor cells, encompassing the regulation of tumor metabolism, immunity, and progression. Additionally, we dissect the complex, bidirectional relationship between lactate and pain, and assess the impact of anesthetics on pain relief, lactate homeostasis, and tumorigenesis.